ANALISIS NILAI-NILAI SOSIAL YANG TERKANDUNG DALAM “FILM TANAH SURGA KATANYA” KARYA DANIAL RIFKI - Maulida Fandani Amelia Putri; Imaniar Purbasari; Irfai Fathurohman (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
This study discussed the social values contained in the film entitled "Tanah Surga Katanya". Social value refers to a community belief in which something is believed to be good and useful in life and can be seen in people's daily lives. This study aimed to foster the chidlren's social values in children through the film "Tanah Surga Katanya". This study used qualitative research methods. The object of this research was the film "Tanah Surga Katanya". Data collection techniques included observation and documentation. The data analysis used in this research was content analysis. The stages in data analysis were data reduction, data presentation, and drawing conclusions with the aim of finding, identifying, processing, and analyzing documents. The results of this study showed that there were 8 social values contained in the film entitled "Tanah Surga Katanya". These social values included (1) love for the homeland, (2) pride in the Indonesian nation, (3) mutual assistance, (4) mutual cooperation, (5) compassion, (6) dedication, (7) responsibility, and (8) care.